A review of the impact of micro- and nanoparticles on freeze-thaw durability of hardened concrete: Mechanism perspective. (20th October 2018) - Ebrahimi, Khashayar; Daiezadeh, Mohammad Javad; Zakertabrizi, Mohammad; Zahmatkesh, Farhad; Habibnejad Korayem, Asghar
Highlights: Additives can be used via four mechanisms to enhance concrete freeze-thaw durability. Despite strength reduction, air bubbles decrease water pressure within ice formation. Less permeability and better pore refinement is achieved by consolidation mechanism. Bridging effect provided by fibers and nanoparticles can control crack propagation. Applying hydrophobic admixtures could reduce the ice formation in internal surfaces. Abstract: Frost resistance is an important factor that can affect the durability of structural concrete. This paper reviews previous studies on freeze-thaw resistance of concrete from the mechanism viewpoint. Observations have revealed that concrete additives can be utilized via different mechanisms to enhance concrete freeze-thaw durability. There are four mechanisms contributing frost resistance: (a) providing extra space for ice expansion in concrete using air bubbles, (b) reducing the porosity of concrete using pozzolans and fillers, (c) containing crack propagation using microfibers, nanotubes and nanosheets, and (d) decreasing water absorption using hydrophobic agents. Each mechanism has been discussed profoundly. However, future investigations are needed to provide a better insight into the grey areas, especially in nanoscale additives and hydrophobic concrete. Researchers should devote more investigations to integrate experiments and extract optimum conditions and dosages for the discussed additives.